Gongylonema infection of wild mammals in Japan and Sardinia (Italy). (2020) - Setsuda, A.; Varcasia, A.; Scala, A.; Ozawa, S.; Yokoyama, M.; Torii, H.; Suzuki, K.; Kaneshiro, Y.; Corda, A.; Dessì, G.; Tamponi, C.; Cabras, P.A.; et al.
Abstract: The gullet worms, classical Gongylonema pulchrum and newly differentiated Gongylonema nepalensis, are prevalent in various mammals in Japan and Sardinia, Italy, respectively. The former species is cosmopolitan in distribution, dwelling in the mucosa of the upper digestive tract of a variety of domestic and wild mammals, and also humans. At present, the geographical distribution of G. nepalensis is known in Nepal and Sardinia, with the nematode having been recorded from the oesophagus of water buffaloes (Nepal), cattle, sheep, goats and wild mouflon (Sardinia). To clarify their natural transmission cycles among domestic and wild mammals, the present study analysed the ribosomal RNA gene (rDNA) and mitochondrial cytochrome c oxidase subunit 1 gene ( cox 1) of worms of various origins: G. pulchrum worms from sika deer, wild boars, Japanese macaques, and feral alien Reeves's muntjacs in Japan, and G. nepalensis worms from a red fox and a wild boar in Sardinia. Although the internal transcribed spacer (ITS) regions of rDNA and partial cox 1 nucleotide sequences of G. pulchrum from native wild mammals in Japan were distinct from those of the worms in cattle, the worms from feral alien Reeves's muntjacs showed the cattle-type ITS genotype and cox 1 cattle-I and II haplotypes. The rDNA and cox 1 nucleotide sequences of G. nepalensis from a red fox in Sardinia were almost identical to those of the worms from domestic and wild ruminants on the island. The ecological interaction between domestic and wild mammals and their susceptibility to different Gongylonema spp. must be considered when trying to elucidate this spirurid's transmission dynamics in nature.